Pengaruh Media Pembelajaran Berbasis Teknologi Terhadap Kemampuan Membaca Permulaan Anak Kelompok B Di Tk Tunas Bangsa Desa Sindang Jaya - Arsita, Sindi Ajeng; Saparahayuningsih, Sri; Indrawati, Indrawati (JURNAL PENA PAUD, 2022)
This study aimed to determine whether there was an effect of Microsoft Power Point media on children's reading ability. The subjects this study were group B children in Tunas Bangsa Kindergarten, Sindang Jaya Village, Sindang Kelingi District, Rejang Lebong Regency, with totally 20 children. The type of this research is quantitative research with the experimental method of pre-experimental design in the form of one group posttest-pretest. Data collection techniques used tests. The data were analyzed by using a paired sample t-test and with the help of SPSS version 25 application. The results of this study showed that there was a positive effect of using learning media based on Microsoft Power Point program technology on the early reading ability of group B children in Tunas Bangsa Kindergarten, Sindang Jaya Village. From the results of this study, teachers are suggested to use technology-based learning media to develop early reading skills. Because this research is only limited to Microsoft PowerPoint, it is recommended for future researchers to conduct research on technology-based learning media other than the Microsoft PowerPoint.